Differences in length of stay by teaching team status in an academic medical center in the Midwestern United States. Issue 2 (15th March 2021) - Walker, Rebekah J.; Segon, Ankur; Good, Jennifer; Nagavally, Sneha; Gupta, Navdeep; Levine, Doug; Neuner, Joan; Egede, Leonard E.
ABSTRACT: Background : Given the high cost of inpatient stays, hospital systems are investigating ways to decrease lengths of stay while ensuring high-quality care. The goal of this study was to determine if patients in teaching teams (hospitalist teams with residents and interns) had a higher length of stay after adjusting for relevant confounders compared to hospitalist-only teams (staffed only by attending physicians). Methods : Using a retrospective design, we investigated differences in length of stay for 17, 577 inpatient encounters over a 2-year period. Length of stay was calculated based on the time between hospital admission and hospital discharge with no removal of outliers. Encounters were assigned to teams based on the discharge provider. Teams were grouped based on whether they were teaching teams or nonteaching teams. Since the length of stay was not normally distributed, it was modeled first using generalized linear models with gamma distribution and log link, and secondly by quantile regression. Models were adjusted for age, gender, race, medicine vs. non-medicine unit, MS-DRGs, and comorbidities. Results : Using gamma models to account for the skewed nature of the data, the length of stay for encounters assigned to teaching teams was 0.56 days longer (β = 0.10 95% CI 0.06 0.14) than for nonteaching teams after adjustment. Using quantile regression, teaching teams had encounters on average 0.63 days longer (95% CI 0.44 0.81) than nonteaching teams at the 75 th percentile and 1.19 days longer (95% CI 0.77 1.61) compared to nonteaching teams at the 90 th percentile after adjustment. Conclusions : After adjusting for demographics and clinical factors, teaching teams on average had lengths of stay that were over half day longer than nonteaching teams. In addition, for the longest encounters, differences between teaching and nonteaching teams were over 1-day difference. Given these results, process improvement opportunities exist within teaching teams regarding length of stay, particularly for longer encounters.